(untitled) (Web of Teachers: Inderscience Research, 2024)
The 21st century has witnessed groundbreaking advancements in linguistics, particularly through the integration of Artificial Intelligence (AI) and Natural Language Processing (NLP). This article explores the intersection of linguistics with AI and NLP technologies, highlighting how these innovations have reshaped our understanding of language, communication, and computational linguistics. The article delves into the evolution of NLP, the development of machine learning models that understand and generate human language, and the impact of AI-driven tools on linguistic research and language teaching. The discussion further covers challenges such as language diversity, computational limitations, and ethical considerations in AI language applications. Ultimately, the article envisions the future of linguistics, proposing a dynamic synergy between human language and artificial intelligence.